Mulheres e corpo: uma investigação sobre os valores de consumo do corpo feminino - Tonini, Karla Andréa Dulce (2016)
The body and its manifestations in consumer society have been part of the list of concerns of academics from different fields of knowledge. The body became an object that can be consumed, and became the centerpiece of a growing market since the second half of the twentieth century having great importance for marketing. The aim of this study is to investigate the consumption figures of the female body, which will contribute to studies in marketing, specifically in the study area of consumer behavior. Thus, there were fifteen in-depth interviews with consumers that, after being written down, were analyzed using the technique of content analysis proposed by Bardin (1977). Holbrook´s (1999) value typology was used as the basis for the categorization of the values of consumption in relation to the female body. Finally, it was possible to identify the types of consumer values proposed by Holbrook, but there were a few discussions about the perfect suitability of this typology to identify consumer values of the female body.